Student’s perception Of Using Beyonces “Eve Maria“ To Motivate English Learning - Cindy yani simorangkir; Selviana Napitupulu (GLOBAL SCIENTS PUBLISHER, 2026)
Music has long been recognized as a powerful educational tool in promoting emotional engagement and enhancing language learning motivation. However, few studies have explored how religious or emotionally expressive songs can be used effectively in English as a Foreign Language (EFL) classrooms, especially within secondary education contexts. This study aims to analyze students’ perceptions toward the use of Beyoncé’s song “Ave Maria” as a medium to motivate English language learning at SMP Cinta Rakyat 3 Pematangsiantar. Employing a descriptive qualitative method, data were collected through classroom observations, open-ended questionnaires, and semi-structured interviews with eighth-grade students. The findings revealed that students demonstrated positive perceptions toward the use of the song, as its melody, emotional tone, and meaningful lyrics enhanced their understanding of vocabulary, pronunciation, and moral values. Moreover, the integration of music created a relaxed and enjoyable classroom atmosphere, which significantly increased students’ enthusiasm and participation. In conclusion, this study suggests that incorporating emotionally rich music, such as “Ave Maria,” can serve as an effective pedagogical tool to foster motivation and engagement in EFL learning environments.